Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard... - Richard Borrmeister (Wikimedia Commons, 1937)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg Ansichtskarte 1937 NSDAP Propaganda Richard BORRMEISTER Verlag Photo-Hoffmann München 37-6 Reichsarbeitdienst RAD emblem Burg Nazi Rally Nuremberg castle Postcard No known copyright restrictions 675726-000000. " Nuremberg Party Rally " (Reichsparteitag Nürnberg). Postcard showing a uniformed member of the Reichsarbeitsdienst (RAD, German Labour Service), the RAD swastika-and-shovel-emblem, and Nuremberg castle | signed R. Borrmeister | published by Verlag Photo Hoffmann, Munich | Nazi Party (NSDAP) propaganda
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Château